Occupational exposure to particulate matter and fungi in a composting plant: case study in Portugal - Viegas, Susana (2014)
The handling of waste can be responsible for occupational exposure to particles and fungi. The aim of this study was to characterize exposure to particles and fungi in a composting plant. Measurements of particulate matter were performed using portable direct-reading equipment. Air samples of 50L were collected through an impaction method with a flow rate of 140L/min onto malt extract agar supplemented with chloramphenicol (0.05%). Surfaces samples were also collected. All the samples were incubated at 27ºC for 5 to 7 days. Particulate matter data showed higher contamination for PM, and PM10 sizes. Aspergillus genus presents the highest air prevalence (90.6%). Aspergillus niger (32.6%), A. fumigatus (26.5%) and A. flavus (16.3%) were the most prevalent fungi in air sampling, and Mucor sp. (39.2%), Aspergillus niger (30.9%) and A. fumigatus (28.7%) were the most found in surfaces. the results obtained claim the attention to the need of further research.